Antibacterial fabric and preparation process thereof

By using antibacterial finishing agents in the fabric, including long-acting antibacterial agents and hydrophobic antibacterial agents, the problem that the fabric is prone to adhere to bacteria after absorbing sweat is solved, achieving better antibacterial performance and anti-fouling effect.

CN119686104AInactive Publication Date: 2025-03-25JIANGYIN JIAMEI KNITTING CLOTHING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510199678.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fabrics tend to adhere to bacteria and fungi after absorbing sweat, resulting in rancidity and health risks, and insufficient antibacterial performance.

Method used

An antibacterial fabric is used that includes a cotton fabric layer and a loaded antibacterial layer, which consists of an antibacterial finishing agent, which includes antibacterial agent, coupling agent and water, and long-acting antibacterial agents and hydrophobic antibacterial agents such as limonene and graft-modified terpineol.

Benefits of technology

It improves the antibacterial properties of the fabric, prevents bacteria from adhesion, enhances the stability and anti-fouling properties of the antibacterial layer, and allows the fabric to maintain good antibacterial effects during high-temperature treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of fabrics, and particularly discloses an antibacterial fabric and a preparation process thereof. The antibacterial fabric comprises a cotton fabric layer and an antibacterial layer loaded on the cotton fabric layer, the antibacterial layer is composed of an antibacterial finishing agent, and the antibacterial finishing agent comprises the following raw materials in parts by weight: 10-20 parts of an antibacterial agent; 2-5 parts of a coupling agent; and the balance of water. The antibacterial agent comprises a long-acting antibacterial agent and a hydrophobic antibacterial agent, the hydrophobic antibacterial agent comprises limonene and terpilenol, the terpilenol is modified terpilenol grafted with a polymer, and the polymer is a polyacrylate copolymer. The preparation method comprises the following steps: S1, preparing the antibacterial finishing agent; s2, preparing the fabric. The fabric can be used in clothes such as POLO shirts and the like, and has the advantages of resisting bacteria, preventing bacterial adhesion and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fabrics, and more specifically, to an antibacterial fabric and a preparation process thereof. Background Art

[0002] Currently, most clothing is made of pure cotton or a blend of pure cotton and polyester. In summer, when the human body secretes more sweat, the fabrics that have absorbed sweat are more likely to adhere to some microorganisms such as bacteria and fungi, which can cause stench and mildew at the very least, and spread diseases at the worst, affecting people's health.

[0003] With the rapid development of industry and the improvement of people's living standards, people have higher and higher requirements for the quality of life and pay more and more attention to the environment and health. Therefore, there is an urgent need to produce a fabric with antibacterial effect. Summary of the invention

[0004] In order to improve the problem of poor antibacterial performance of fabrics, the present application provides an antibacterial fabric and a preparation process thereof, which adopts the following technical solutions: In a first aspect, the present application provides an antibacterial fabric, comprising a cotton fabric layer and an antibacterial layer loaded on the cotton fabric layer, wherein the antibacterial layer is composed of an antibacterial finishing agent, and the antibacterial finishing agent comprises the following raw materials in parts by weight: 10-20 parts of antibacterial agent; 2-5 parts of coupling agent; The antibacterial agent comprises a long-acting antibacterial agent and a hydrophobic antibacterial agent, wherein the hydrophobic antibacterial agent comprises limonene and pinene alcohol, wherein the pinene alcohol is a modified pinene alcohol grafted with a polymer, and the polymer is a polyacrylate copolymer.

[0005] By adopting the above technical scheme, the cotton fabric has better air permeability, hygroscopicity and degradability, and is more comfortable to wear in summer. Limonene and terpineol are preferably used as hydrophobic antibacterial agents. Both limonene and terpineol are terpenoid compounds with a single ring and a three-dimensional structure, so that both limonene and terpineol have better antibacterial, anti-inflammatory, antioxidant and other properties, and are plant raw materials, environmentally friendly and not easy to cause skin allergies, so that the antibacterial fabric obtains excellent antibacterial effect; and due to the presence of the three-dimensional structure of limonene and terpineol, the bacterial perception system can be affected, so that the bacteria actively do not adhere to the surface of the fabric, giving limonene and terpineol excellent antibacterial adhesion effect, so the antibacterial layer can effectively prevent bacteria from adhering to the surface of the antibacterial fabric, further improving the antibacterial effect of the antibacterial fabric.

[0006] The present application preferably grafts a polyacrylate copolymer onto pinene alcohol, and utilizes an esterification reaction to achieve the combination of pinene alcohol and the polyacrylate copolymer. Since the polyacrylate copolymer has good thermal stability and acid stability, the thermal stability and acid stability of pinene alcohol can be improved after grafting, so that the antibacterial fabric can stably play an anti-adhesion and antibacterial role during high-temperature drying, baking and ironing treatments; and in the post-finishing process, pinene alcohol is not easy to change, so that the antibacterial fabric obtains stable antibacterial adhesion and antibacterial effects.

[0007] Optionally, the modified pinene alcohol is prepared as follows: tetrahydrofuran, acrylic anhydride and DMAP are added to a container, stirred at a constant temperature to obtain a mixed solution, pinene alcohol is added to the mixed solution, the reaction is continued to obtain an intermediate solution, ammonium persulfate is added to the intermediate solution, a polymerization reaction is carried out, the solution is cooled, filtered, the solid matter is retained, washed, and dried to obtain the modified pinene alcohol.

[0008] By adopting the above technical scheme, pinene alcohol and acrylic anhydride are grafted through an esterification reaction, and polymerization occurs under the initiation of ammonium persulfate, and finally pinene alcohol grafted with a polyacrylate copolymer is obtained.

[0009] Optionally, the molar ratio of the terpineol to the acrylic anhydride is 2-2.5:1.

[0010] By adopting the above technical scheme, the molar ratio of pineol to acrylic anhydride is optimized. At an appropriate molar ratio, the higher the graft esterification rate between pineol and acrylic anhydride, the more reactants participate in the polymerization, and the content of pineol in the obtained modified pineol is higher, which can enable the antibacterial layer to obtain excellent antibacterial adhesion effect.

[0011] Optionally, the modified pinene alcohol is prepared as follows: tetrahydrofuran, acrylic anhydride and DMAP are added to a container, stirred at a constant temperature to obtain a mixed solution, pinene alcohol is added to the mixed solution, the reaction is continued to obtain an intermediate solution, ammonium persulfate and 2-hydroxyethyl methacrylate are added to the intermediate solution, a polymerization reaction is carried out, the solution is cooled, filtered, the solid matter is retained, washed, and dried to obtain the modified pinene alcohol.

[0012] By adopting the above technical scheme, the preparation process of modified pineol is optimized. 2-hydroxyethyl methacrylate is added at the same time as ammonium persulfate, so that 2-hydroxyethyl methacrylate can participate in the polymerization. Since 2-hydroxyethyl methacrylate has good biocompatibility, the modified pineol can obtain better biocompatibility, the destructiveness of the antibacterial layer to bacteria is enhanced, and the antibacterial effect of the antibacterial layer is further improved.

[0013] Optionally, the long-acting antibacterial agent includes titanium dioxide and nanosilver.

[0014] By adopting the above technical scheme, titanium dioxide has excellent photocatalytic activity, and there are many defects in the lattice. Under illumination conditions, photogenerated electrons can be generated, and then react with oxygen and water to produce free radicals. The free radicals have strong oxidizing ability, and can oxidize organic matter into carbon dioxide and water, and can also destroy the biological cell structure, leading to cell death, that is, it has better self-cleaning and antibacterial effects. Nanosilver can be adsorbed on the surface of bacterial cell membranes, destroy the cell membrane and puncture into the interior of bacterial cells, thereby affecting the penetration and respiratory function of cells to achieve the antibacterial effect of nanosilver. It is preferred to use titanium dioxide and nanosilver in combination as long-acting antibacterial agents, so that the antibacterial layer can obtain excellent self-cleaning performance and long-term antibacterial effect.

[0015] Optionally, the nanosilver is deposited on titanium dioxide.

[0016] By adopting the above technical solution, since nanosilver is deposited on the surface of titanium dioxide, photogenerated electrons can be transferred from the conduction band of titanium dioxide to nanosilver located on the surface of titanium dioxide with a lower Fermi level, and the photogenerated holes on the titanium dioxide still exist, which reduces the recombination rate of electron-hole pairs and enhances the photocatalytic activity of titanium dioxide, thereby further improving the antifouling performance and antibacterial strength of the antibacterial layer.

[0017] Optionally, the titanium dioxide and the nanosilver are loaded on chitosan.

[0018] By adopting the above technical solution, titanium dioxide and nanosilver are loaded with chitosan, so that titanium dioxide and nanosilver can form a micro-nano structure on the surface of the antibacterial layer. The micro-nano structure has a better hydrophobic effect and can further improve the antifouling performance of the antibacterial fabric. At the same time, chitosan has a better antibacterial effect, so it can further improve the antibacterial effect of the antibacterial layer.

[0019] Optionally, the coupling agent includes polydimethylsiloxane and coupling agent KH560.

[0020] By adopting the above technical solution, preferably using polydimethylsiloxane and coupling agent KH560 as coupling agent, not only can the bonding effect between the antibacterial layer and the cotton fabric be improved, but also the antibacterial layer can be given an excellent hydrophobic effect, effectively improving the antifouling effect and antibacterial performance of the antibacterial fabric. At the same time, due to the presence of coupling agent KH560, it can react with chitosan to improve the dispersion of chitosan in the antibacterial finishing liquid, effectively improve the strength between chitosan and cotton fabric, and enable the fabric to obtain a uniform and stable antibacterial effect.

[0021] Optionally, the long-acting antibacterial agent further comprises essential oil microcapsules, and the essential oil microcapsules are selected from any one or more of tea tree essential oil microcapsules, lavender microcapsules, tangerine peel essential oil microcapsules or orange peel essential oil microcapsules.

[0022] By adopting the above technical scheme, it is preferred to add essential oil microcapsules to the long-acting antibacterial agent. The essential oil microcapsules have a better sustained-release effect, and the plant essential oils also have a better antibacterial effect, which can enable the antibacterial fabric to obtain long-lasting aromatic properties and antibacterial effects, and effectively improve the wearing effect of the antibacterial fabric.

[0023] In a second aspect, the present application provides a method for preparing an antibacterial fabric, which adopts the following technical solution: A method for preparing an antibacterial fabric comprises the following steps: S1. Preparation of antibacterial finishing agent: respectively mixing an antibacterial agent, a coupling agent and water to obtain an antibacterial finishing agent solution; S2. Fabric preparation: immerse the cotton fabric in the antibacterial finishing agent solution at a bath ratio of 1:30-40, perform two immersions and two rollings, and achieve a rolling rate of 60-70%. Take out the fabric, pre-bake, bake, wash, and air-dry to obtain the antibacterial fabric.

[0024] By adopting the above technical solution, the cotton fabric layer is treated by the dipping method, so that the effective substances in the antibacterial treatment liquid are fully absorbed by the cotton fabric layer, thereby enabling the antibacterial fabric to obtain uniform and excellent antibacterial and anti-pollution effects.

[0025] In summary, this application has the following beneficial effects: 1. Since the present application preferably uses limonene and pinene alcohol as hydrophobic antibacterial agents, the presence of the three-dimensional structure of limonene and pinene alcohol can affect the bacterial perception system, so that the bacteria actively do not adhere to the surface of the fabric, giving limonene and pinene alcohol excellent antibacterial adhesion effect, so the antibacterial layer can effectively prevent bacteria from adhering to the surface of the antibacterial fabric. Polyacrylate copolymers are grafted onto pinene alcohol, and the combination between pinene alcohol and polyacrylate copolymers is achieved by esterification reaction. Since polyacrylate copolymers have good thermal stability and acid stability, the thermal stability and acid stability of pinene alcohol can be improved after grafting, so that the antibacterial fabric can stably play an anti-adhesion and antibacterial role during high-temperature drying, baking and ironing.

[0026] 2. The preparation process of modified pineol is optimized in the present application. 2-hydroxyethyl methacrylate is added at the same time as ammonium persulfate, so that 2-hydroxyethyl methacrylate participates in the polymerization. Since 2-hydroxyethyl methacrylate has good biocompatibility, the modified pineol can obtain better biocompatibility, the destructiveness of the antibacterial layer to bacteria is enhanced, and the antibacterial effect of the antibacterial layer is further improved.

[0027] 3. The present application uses chitosan to load titanium dioxide and nanosilver, so that titanium dioxide and nanosilver can form a micro-nano structure on the surface of the antibacterial layer. The micro-nano structure has a good hydrophobic effect and can further improve the antifouling performance of the antibacterial fabric. At the same time, chitosan has a good antibacterial effect, so it can further improve the antibacterial effect of the antibacterial layer. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] In the examples of the present application, the drugs used are as follows, but not limited thereto: Tetrahydrofuran: analytical grade, MacLean; Acrylic anhydride: analytical grade, MacLean; DMAP: analytical grade, MacLean; α-Terpineol: analytical grade, MacLean; Ammonium persulfate: analytical grade, MacLean; Titanium dioxide: HN-TG0 type from Hangzhou Hengna New Materials Co., Ltd.; Silver nitrate: analytical grade, Sinopharm Chemical Reagent; Ammonia: 25%, Sinopharm Chemical Reagent; Sodium borohydride: analytical grade, Sinopharm Chemical Reagent; Ethanol: analytical grade, MacLean; Chitosan: Deacetylation degree 80-95, Sinopharm Chemical Reagents; Acetic acid: analytical grade, MacLean; Liquid paraffin: analytical grade, MacLean; Span-80: analytical grade, Shanghai McLean Biochemical Technology Co., Ltd.; Isopropanol: analytical grade, MacLean; Trimethylammonium chloride: analytical grade, Shanghai McLean Biochemical Technology Co., Ltd.; Urea: MacLean; Titanyl sulfate: 93%, McLean; Nanosilver: Nanosilver from Hebei Mutun Mineral Products Co., Ltd.; D-limonene: analytical grade, MacLean; Polydimethylsiloxane: analytical grade, MacLean; Coupling agent KH560: analytical grade, MacLean; 2-Hydroxyethyl methacrylate: 96%, Aladdin reagent.

[0030] Preparation Example Preparation example of modified terpineol Preparation Example 1 Add 50 mL of tetrahydrofuran, 50 mmol of acrylic anhydride and 10 mg of DMAP into a container, stir at a constant temperature of 70° C. to obtain a mixed solution, add 0.1 mol of pinene alcohol to the mixed solution, continue the reaction to obtain an intermediate solution, add 1% of the total system mass of ammonium persulfate to the intermediate solution, polymerize at 70° C. for 5 hours, cool, filter, retain the solid, wash three times with ethanol, and dry to obtain modified pinene alcohol.

[0031] Preparation Example 2 Add 50 mL of tetrahydrofuran, 50 mmol of acrylic anhydride and 10 mg of DMAP into a container, stir at a constant temperature of 70° C. to obtain a mixed solution, add 0.125 mol of pinene alcohol to the mixed solution, continue the reaction to obtain an intermediate solution, add 1% of the total system mass of ammonium persulfate to the intermediate solution, polymerize at 70° C. for 5 h, cool, filter, retain the solid, wash three times with ethanol, and dry to obtain modified pinene alcohol.

[0032] Preparation Example 3 Add 50 mL of tetrahydrofuran, 50 mmol of acrylic anhydride and 10 mg of DMAP into a container, stir at a constant temperature of 70° C. to obtain a mixed solution, add 0.1 mol of pinene alcohol to the mixed solution, continue the reaction to obtain an intermediate solution, add 2% of the total system mass of ammonium persulfate and 10 mmol of 2-hydroxyethyl methacrylate to the intermediate solution, polymerize at 70° C. for 5 h, cool, filter, retain the solid, wash three times with ethanol, and dry to obtain modified pinene alcohol.

[0033] Preparation Example of Nanosilver Deposited Titanium Dioxide Preparation Example 4 0.2g of titanium dioxide was dispersed in 100mL of distilled water and ultrasonically dispersed for 5min. Then, the corresponding mass of silver nitrate was weighed according to the mass fraction of titanium dioxide of 15%, and then added to the solution for ultrasonication for 5min. Then, the pH of the solution was adjusted to 10 with ammonia water and magnetically stirred for 10min to obtain liquid A. Sodium borohydride with the same molar number as silver nitrate was weighed and dissolved in 10mL of distilled water to obtain liquid B. Then, liquid A and liquid B were mixed and ultrasonically dispersed for 30min. Then, the precipitate was collected by centrifugation at a speed of 5000r / m for 30min, and the precipitate was washed with ethanol. Finally, it was dried in a drying furnace at 50°C overnight to obtain titanium dioxide with surface Ag deposition.

[0034] Preparation example of titanium dioxide and nano silver loaded on chitosan Preparation Example 5 The preparation process of the titanium dioxide and the nanosilver loaded on chitosan is as follows: 1.5g chitosan is dissolved in 100mL acetic acid solution with a volume fraction of 1.5% to obtain a CS solution; 4mL span-80 is mixed with 96mL liquid paraffin to obtain a span solution; 10mL CS solution is mixed with 100mL span solution, 0.4mL glutaraldehyde is added, cross-linking reaction is carried out, washing, and drying is carried out to obtain an intermediate product; the intermediate product is mixed with isopropanol to obtain a mixed solution, trimethylammonium chloride is added to the mixed solution, reacted at 70°C, frozen at -15°C for 2h, washed, and dried to obtain a primary product. 0.15g product, 0.8g urea, 0.08g titanyl sulfate and 40mL water are mixed, reacted at 160°C for 3h, washed with water, and dried to obtain a secondary product, 0.3g secondary product, 1mL (0.01mol / L) silver nitrate aqueous solution and 200mL water are mixed, irradiated under a xenon lamp for 2h, filtered, washed, and the final product is obtained.

[0035] Example Examples 1-3 On the one hand, the present application provides an antibacterial fabric, including a cotton fabric layer and an antibacterial layer loaded on the cotton fabric layer, wherein the antibacterial layer is composed of an antibacterial finishing agent, and the antibacterial finishing agent includes the following raw materials: an antibacterial agent, a coupling agent and water, and the specific mass is shown in the table below.

[0036] The antibacterial agent includes a long-acting antibacterial agent and a hydrophobic antibacterial agent in an equal weight ratio, and the long-acting antibacterial agent includes nanosilver and titanium dioxide in an equal weight ratio. The hydrophobic antibacterial agent includes limonene and the modified pinene prepared in Preparation Example 1 in an equal weight ratio. The coupling agent includes polydimethylsiloxane and coupling agent KH560 in an equal weight ratio.

[0037] On the other hand, the present application provides a process for preparing an antibacterial fabric, comprising the following steps: S1, preparation of an antibacterial finishing agent: respectively taking an antibacterial agent, a coupling agent and water and mixing them to obtain an antibacterial finishing agent solution; S2. Fabric preparation: The cotton fabric is immersed in the antibacterial finishing agent solution at a bath ratio of 1:30, twice immersed and twice rolled, and the rolling rate is 70%. The fabric is taken out, pre-dried, baked, washed, and dried to obtain the antibacterial fabric.

[0038] Table 1 Composition of antibacterial finishing agent solution in Example 1-3

[0039] Example 4 The difference from Example 3 is that in this example, the hydrophobic antibacterial agent includes limonene and the modified terpineol prepared in Preparation Example 2 in equal amounts.

[0040] Example 5 The difference from Example 3 is that in this example, the hydrophobic antibacterial agent includes limonene and the modified terpineol prepared in Preparation Example 3 in equal amounts.

[0041] Example 6 The difference from Example 3 is that in this example, the long-acting antibacterial agent includes the titanium dioxide with surface Ag deposition obtained in Preparation Example 4.

[0042] Example 7 The difference from Example 3 is that in this example, the long-acting antibacterial agent includes titanium dioxide and nano-silver, and the titanium dioxide and nano-silver are loaded on chitosan. The specific preparation method is shown in Preparation Example 5.

[0043] Example 8 The difference from Example 7 is that in this example, the long-acting antibacterial agent includes tea tree essential oil microcapsules, titanium dioxide and nanosilver, wherein the titanium dioxide and nanosilver are loaded on chitosan, and the specific preparation method is as shown in Preparation Example 5.

[0044] Example 9 The difference from Example 5 is that in this example, the long-acting antibacterial agent includes tea tree essential oil microcapsules, titanium dioxide and nanosilver, wherein the titanium dioxide and nanosilver are loaded on chitosan, and the specific preparation method is as shown in Preparation Example 5.

[0045] Comparative Example Comparative Example 1 The difference between this comparative example and Example 3 is that the hydrophobic antibacterial agent in this comparative example includes terpineol and limonene in equal amounts.

[0046] Comparative Example 2 The difference between this comparative example and Example 3 is that this comparative example only includes a hydrophobic antibacterial agent.

[0047] Performance testing (1) Anti-bacterial adhesion performance: A scanning electron microscope was used to observe the bacterial adhesion on the surface of cotton fabrics before and after finishing. Escherichia coli and Staphylococcus aureus were used to test the anti-adhesion performance of anti-adhesion fabrics. The anti-adhesion rate was calculated according to the following formula: Anti-adhesion rate = (AB) / A×100%, where A and B represent the total number of bacteria adhering to the untreated fabric and the treated fabric, respectively.

[0048] (2) Antibacterial performance testing: According to the test method in GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the antibacterial properties of antibacterial fabrics were evaluated using Staphylococcus aureus ATCC6538 and Escherichia coli ATCC25922.

[0049] (3) Self-cleaning test: Refer to GB / T30159.1-2013 "Testing and evaluating the antifouling performance of textiles Part 1: Antifouling" standard, and use dried and ground coffee grounds powder as the pollutant. Use tape to fix the fabric sample on a glass slide, and place the glass slide at an angle. Use coffee grounds to pollute the surface of the fabric sample, and drop distilled water on the surface of the fabric sample. The self-cleaning performance of the fabric sample is evaluated by the residual coffee grounds pollutant on the surface of the fabric sample.

[0050] (4) Hydrophobic performance test: At room temperature, 5 locations on the fabric surface were randomly selected for testing. The volume of each droplet was 3 μL, and the water contact angle was tested.

[0051] Table 2 Performance test

[0052] Combining the performance test comparison in Table 2, we can find that: 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the antibacterial properties, anti-adhesion properties, hydrophobic properties and self-cleaning effects of the antibacterial fabrics prepared in Examples 1-3 are all improved, which indicates that the presence of the three-dimensional structure of limonene and terpineol in the present application can affect the bacterial perception system, so that the bacteria actively do not adhere to the surface of the fabric, and give limonene and terpineol excellent antibacterial adhesion effects. The combination of terpineol and polyacrylate copolymer is achieved by esterification reaction. Since the polyacrylate copolymer has good thermal stability and acid stability, the thermal stability and acid stability of terpineol can be improved after grafting, so that the antibacterial fabric can stably play an anti-adhesion and antibacterial role during high-temperature drying, baking and ironing.

[0053] 2. By comparing Example 4 with Example 3, it can be found that the antibacterial properties, anti-adhesion properties, hydrophobicity and self-cleaning effects of the antibacterial fabric prepared in Example 4 are all improved, which indicates that the molar ratio of pineol to acrylic anhydride is optimized in the present application. At a suitable molar ratio, the higher the graft esterification rate between pineol and acrylic anhydride, the more reactants participate in the polymerization, and the higher the content of pineol in the modified pineol, which can enable the antibacterial layer to obtain excellent antibacterial adhesion effect.

[0054] 3. By comparing Example 5 with Example 3, it can be found that the antibacterial property, anti-adhesion property, hydrophobicity and self-cleaning effect of the antibacterial fabric prepared in Example 5 are improved, which means that in the present application, 2-hydroxyethyl methacrylate is added at the same time as ammonium persulfate, so that 2-hydroxyethyl methacrylate participates in the polymerization. Since 2-hydroxyethyl methacrylate has good biocompatibility, the modified pinene alcohol can obtain better biocompatibility, so that the antibacterial layer is more destructive to bacteria, and the antibacterial effect of the antibacterial layer is further improved.

[0055] 4. By comparing Example 6 with Example 3, it can be found that the antibacterial property, anti-adhesion property, hydrophobicity and self-cleaning effect of the antibacterial fabric prepared in Example 6 are all improved, which means that in the present application, since the nanosilver is deposited on the surface of titanium dioxide, the photogenerated electrons can be transferred from the conduction band of titanium dioxide to the nanosilver with a lower Fermi level located on the surface of titanium dioxide, and the photogenerated holes on the titanium dioxide still exist, which reduces the recombination rate of electron-hole pairs and enhances the photocatalytic activity of titanium dioxide, thereby further improving the antifouling performance and antibacterial strength of the antibacterial layer.

[0056] 5. By comparing Example 7 with Example 3, it can be found that the antibacterial property, anti-adhesion property, hydrophobicity and self-cleaning effect of the antibacterial fabric prepared in Example 7 are all improved, which means that the use of chitosan to load titanium dioxide and nano-silver in the present application can form a micro-nano structure of titanium dioxide and nano-silver on the surface of the antibacterial layer. The micro-nano structure has a better hydrophobic effect and can further improve the antifouling performance of the antibacterial fabric.

[0057] 6. By comparing Examples 8-9 with Example 3, it can be found that the antibacterial properties, anti-adhesion properties, hydrophobicity and self-cleaning effects of the antibacterial fabrics prepared in Examples 8-9 are improved, which means that in the present application, the essential oil microcapsules are added to the long-acting antibacterial agent, the essential oil microcapsules have a better sustained-release effect, and the plant essential oils also have a better antibacterial effect, which can enable the antibacterial fabrics to obtain lasting aromatic properties and antibacterial effects, and effectively improve the wearing effect of the antibacterial fabrics.

[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An antibacterial fabric, characterized in that: It comprises a cotton fabric layer and an antibacterial layer loaded on the cotton fabric layer, wherein the antibacterial layer is composed of an antibacterial finishing agent, and the antibacterial finishing agent comprises the following raw materials in parts by weight: 10-20 parts of antibacterial agent; 2-5 parts of coupling agent; water balance; the antibacterial agent includes a long-acting antibacterial agent and a hydrophobic antibacterial agent, the hydrophobic antibacterial agent includes limonene and pinene alcohol, the pinene alcohol is a modified pinene alcohol grafted with a polymer, and the polymer is a polyacrylate copolymer; the modified pinene alcohol is prepared as follows: tetrahydrofuran, acrylic anhydride and DMAP are added to a container, stirred at a constant temperature to obtain a mixed solution, pinene alcohol is added to the mixed solution, the reaction is continued to obtain an intermediate solution, ammonium persulfate is added to the intermediate solution, polymerization reaction is carried out, cooling, suction filtration, retaining solid matter, washing, drying, and obtaining modified pinene alcohol.

2. The antibacterial fabric according to claim 1, characterized in that: The molar ratio of the terpineol to the acrylic anhydride is 2-2.5:

1.

3. The antibacterial fabric according to claim 2, characterized in that: The modified pinene alcohol is prepared as follows: tetrahydrofuran, acrylic anhydride and DMAP are added to a container, stirred at a constant temperature to obtain a mixed solution, pinene alcohol is added to the mixed solution, the reaction is continued to obtain an intermediate solution, ammonium persulfate and 2-hydroxyethyl methacrylate are added to the intermediate solution, polymerization reaction is carried out, cooling, suction filtration, retaining solids, washing, and drying to obtain modified pinene alcohol.

4. The antibacterial fabric according to claim 3, characterized in that: The long-acting antibacterial agent comprises titanium dioxide and nano silver.

5. The antibacterial fabric according to claim 4, characterized in that: The nanosilver is deposited on titanium dioxide.

6. The antibacterial fabric according to claim 5, characterized in that: The titanium dioxide and the nano silver are loaded on chitosan.

7. The antibacterial fabric according to claim 1, characterized in that: The coupling agent includes polydimethylsiloxane and coupling agent KH560.

8. The antibacterial fabric according to claim 1, characterized in that: The long-acting antibacterial agent further comprises essential oil microcapsules, and the essential oil microcapsules are selected from any one or more of tea tree essential oil microcapsules, lavender microcapsules, tangerine peel essential oil microcapsules or orange peel essential oil microcapsules.

9. The process for preparing an antibacterial fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of antibacterial finishing agent: respectively mixing an antibacterial agent, a coupling agent and water to obtain an antibacterial finishing agent solution; S2. Fabric preparation: immerse the cotton fabric in the antibacterial finishing agent solution at a bath ratio of 1:30-40, perform two immersions and two rollings, and achieve a rolling rate of 60-70%. Take out the fabric, pre-bake, bake, wash, and air-dry to obtain the antibacterial fabric.

Citation Information

Patent Citations

  • Waterproof antibacterial fabric finishing agent and application thereof

    CN111321594A

  • Ecological durable antibacterial and bacterial adhesion prevention dual-function fabric and preparation method thereof

    CN116377717A

  • Antibacterial antimony-free low-melting-point yarn and production method thereof

    CN116446179A

  • Antimicrobial yarn and production thereof

    JP1990307913A